1992
DOI: 10.1093/nar/20.15.3821
|View full text |Cite
|
Sign up to set email alerts
|

Thiordoxin regulates the DNA binding activity of NF-χB by reduction of a disulphid bond involving cysteine 62

Abstract: A role for redox regulation in activation of the NF-kappa B transcription factor was suggested by the observation that DNA binding activity of free protein, but not preformed DNA-protein complex, is inhibited by -SH modifying agents but enhanced by reducing agents. Mutagenesis of conserved cysteine residues in the p50 subunit identified amino acid 62 as being important for DNA binding, as a serine substitution at this position reduces DNA binding affinity, but renders the protein insensitive to -SH modifying a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
487
0
8

Year Published

1994
1994
2007
2007

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 772 publications
(509 citation statements)
references
References 62 publications
14
487
0
8
Order By: Relevance
“…This finding is in agreement with the observations of others who demonstrated a similar specificity in NFκB activation in both normal and malignant cells following exposure to thiol-containing drugs such as N-acetyl-L-cysteine, dithiothreitol, 2-mercaptoethanol, WR1065, and oltipraz [14,16,18]. This is not surprising since NFκB is a well-characterized redox-sensitive transcription factor whose activation is known to be induced by both oxidative stress [14][15][16][17][18] and reducing agents that are capable of altering the redox state of the cysteine 62 residue of its p50 subunit [35]. Correlating with NFκB activation is the robust expression of the MnSOD gene.…”
Section: Discussionmentioning
confidence: 96%
“…This finding is in agreement with the observations of others who demonstrated a similar specificity in NFκB activation in both normal and malignant cells following exposure to thiol-containing drugs such as N-acetyl-L-cysteine, dithiothreitol, 2-mercaptoethanol, WR1065, and oltipraz [14,16,18]. This is not surprising since NFκB is a well-characterized redox-sensitive transcription factor whose activation is known to be induced by both oxidative stress [14][15][16][17][18] and reducing agents that are capable of altering the redox state of the cysteine 62 residue of its p50 subunit [35]. Correlating with NFκB activation is the robust expression of the MnSOD gene.…”
Section: Discussionmentioning
confidence: 96%
“…Abate et al (24) demonstrated that the DNA binding activity of c-Fos and c-Jun is sensitive to reversible cysteine oxidation at amino acids 154 and 252, respectively. NF-B is also subject to redox regulation on cysteine 62 on the p50 subunit (49). The DNA binding activity of the transcription factor is inhibited by oxidation (23).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, an important component of mammalian cell responses to oxidative stress involves the oxidation of active cysteines in many types of proteins, thereby regulating several activities. Some transcription factors, such as activator protein-1 and nuclear factor-B (NF-B) bear oxidation-sensitive cysteines and they are regulated through oxidation during oxidative stress (Abate et al, 1990;Toledano and Leonard, 1991;Matthews et al, 1992). The formation of intramolecular disulfides in the catalytic core of many phosphatases, including protein tyrosine phosphatase and lipid phosphatases such as phosphatase with sequence homology to tensin (PTEN), results in their reversible inhibition (Lee et al, 2002;Rhee et al, 2005;Salmeen and Barford, 2005;Stone and Yang, 2006).…”
Section: Ask1 Is Oxidized During Oxidative Stressmentioning
confidence: 99%
“…Thioredoxin also contributes to H 2 O 2 scavenging by recycling oxidized peroxiredoxins, an important thiol-based peroxidase family enzyme (Rhee et al, 2005). Thioredoxin as a thiol reductase has also regulatory functions, capable of reducing, either directly or indirectly, several redox-sensitive transcriptional factors (Matthews et al, 1992;Hirota et al, 1997Hirota et al, , 1999Ueno et al, 1999).…”
Section: Introductionmentioning
confidence: 99%